Coupling Between Bacteriochlorophyll and Membrane Protein Synthesis in Rhodopseudomonas spheroides - Takemoto, J. (1973)
Bacteriochlorophyll-containing membranes from Rhodopseudomonas spheroides contain proteins with estimated molecular weights of 26,000, 22,000, 19,000, and 10,000-6,000 (proteins 9, 10, 11, and 15) when analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Proteins 9, 10, and 11 may be associated with the reaction center form of bacteriochlorophyll and protein 15, with the light-harvesting form. These proteins were not detected in membranes from nonpigmented wild-type cells grown with high aeration. Proteins 10, 11, and 15 were not found in mutants with blocks in bacteriochlorophyll synthesis, including strain 8-17, which is blocked at the phytolation step. Protein 9 was found in significantly reduced amounts. Apparently, synthesis of the completed bacteriochlorophyll molecule is required for the occurrence of these proteins in the membrane. Gel autoradiography was used to follow the synthesis of membrane proteins in mutant H-5, which requires δ-aminolevulinic acid for bacteriochlorophyll synthesis. Incorporation of labeled amino acids into proteins 9 and 15 was curtailed preferentially in cells deprived of δ-aminolevulinic acid.